2015
DOI: 10.3389/fphy.2015.00086
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Wettability Alteration in Immiscible Two-phase Flow in Porous Media: Effect on Transport Properties and Critical Slowing Down

Abstract: The change in contact angles due to the injection of low salinity water or any other wettability altering agent in an oil-rich porous medium is modeled by a network model of disordered pores transporting two immiscible fluids. We introduce a dynamic wettability altering mechanism, where the time dependent wetting property of each pore is determined by the cumulative flow of water through it. Simulations are performed to reach steady-state for different possible alterations in the wetting angle (θ). We find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…We leave for future work the problem of how other types of non-uniform wetting conditions can affect the rheology further. A mechanism for a correlated wettability distribution for pore-network modeling, where the wettability depends on the connected oil paths, was demonstrated previously by some of the authors of this manuscript (Flovik et al 2015) and may be adopted in future.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…We leave for future work the problem of how other types of non-uniform wetting conditions can affect the rheology further. A mechanism for a correlated wettability distribution for pore-network modeling, where the wettability depends on the connected oil paths, was demonstrated previously by some of the authors of this manuscript (Flovik et al 2015) and may be adopted in future.…”
Section: Introductionmentioning
confidence: 69%
“…These experimental findings show the importance of understanding the effect of wettability even further, which is easier to do through analytical and numerical studies where large range of wetting conditions can be examined in short time. In the papers by Sinha et al (2011) and Flovik et al (2015), pore network models similar to the one used in the present article were used to investigate the effect of wettability alteration due to changes in salinity in oil-brine mixtures. The wettability alterations were done by changing between either complete wetting and complete non-wetting conditions in the first article (Sinha et al 2011), and by changing the wetting angles continuously between two limits depending on the cumulative flow of the wetting phase in the second article (Flovik et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also note that important phenomena such as wetting angle hysteresis is straight-forward to implement but it has not been included so far. However, wetting angle alteration due to changes in the composition of the immiscible fluids has been considered in the past [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the increase in water wetness during water ooding leads to a higher oil recovery and less accumulated production water at a water cut. Flovik et al (2015) modeled the change in contact angles due to the injection of wettability altering agent in an oil-rich porous medium by a network of disordered pores transporting two immiscible uids [21]. In this article, the authors introduced a dynamic wettability altering mechanism, where the time dependent wetting property of each pore is determined by the cumulative ow of water through it.…”
Section: Introductionmentioning
confidence: 99%